Assessing Disaster-Related Health Risk: Appraisal for Prevention. Issue 3 (1st June 2018) - Keim, Mark
Abstract: Risk assessment is a key component of public health interventions intended to prevent or reduce adverse health effects. Health risk assessments are widely used to guide public health programming, as well as multi-sectoral studies of environmental impact and developmental decision making. Analytical risk assessment is a well-validated tool that is routinely used among certain subsets of public health, including those for chemical, radiological, and microbiological risk assessment. However, this is not the case for risk assessments involving disasters in general, or more specifically, for public health emergencies involving environmental hazards (eg, technological, hydro-meteorological, and seismic). There remains a need for a reproducible, well-validated, disaster-related health risk assessment process that is suitable for accommodating the current gaps in certainty. This report is intended to offer a practical framework and nomenclature for assessing disaster-related health risk that is: (1) accurate; (2) based upon historical evidence; (3) quantifiable in public health terms; and (4) inclusive of uncertainty. M Keim .Assessing disaster-related health risk: appraisal for prevention .Prehosp Disaster Med .2018 ;33 (3 ):317 -325 .